MRI-Based Mapping of Cerebral Propagation in Amyotrophic Lateral Sclerosis - Müller, Hans-Peter; Kassubek, Jan (Frontiers in Neuroscience, 2018)
Neuropathological studies in amyotrophic lateral sclerosis (ALS) have shown that ALS may disseminate in a regional sequence in four disease-related patterns. Diffusion tensor imaging (DTI)-based analysis of MRI data was established for the individual mapping of sequential disease spreading in ALS as the in vivo transfer to neuroimaging. The aim of this review is to summarize cross-sectional and longitudinal results of these technical approaches in ALS as an in vivo tool to image ALS propagation stages. This concept was also applied to restricted phenotypes of ALS, e.g. lower motor neuron disease (LMND) or primary lateral sclerosis (PLS). In summary, in vivo mapping of the disease patterns in ALS has become feasible both cross-sectionally and longitudinally and has the potential to be used as a readout in clinical trials.